Expression of CdDHN4, a Novel YSK2-Type Dehydrin Gene from Bermudagrass, Responses to Drought Stress through the ABA-Dependent Signal Pathway - Lv, Aimin; Fan, Nana; Xie, Jianping; Yuan, Shili; An, Yuan; Zhou, Peng (Frontiers in Plant Science, 2017)
Dehydrin can response to many abiotic-stresses and improves plant resistance ability. In this study, the expression profiles of a dehydrin gene, named CdDHN4, was estimated under different stresses and abscisic acid (ABA) treatment in two bermudagrasses (Cynodon dactylon L.), which are ‘Tifway’ (drought-tolerant) and ‘C299’ (drought-sensitive). The expression levels of CdDHN4 were up-regulated by high temperature, low temperature, drought, salt and ABA addition. The sensitivity of CdDHN4 to ABA and the expression of CdDHN4 under drought condition were higher in ‘Tifway’ than ‘C299’. A 1239bp fragment named CdDHN4-P, which was the partial upstream sequence of the CdDHN4 gene, was cloned with genomic walking from ‘Tifway’. Bioinformatics analysis showed that the CdDHN4-P sequence possessed typical features of plant promoter and contained many typical cis-elements, including transcription initiation site, TATA-box, ABRE, MBS, MYC, LTRE, TATC-box and GT1-motif. It was proved by transient expression in tobacoo leaves that the promoter CdDHN4-P could be activated by ABA, drought and cold. These results indicate that the CdDHN4 is regulated by ABA-dependent signal pathway, and the high sensitivity of CdDHN4 to ABA might be an important mechanism to enhance the drought tolerance of bermudagrass.